Shelf-Life and Quality of Cauliflower (Brassica Oleracea L. Var Botrytis) as Affected by the Type of Polymeric Films and Duration of Modified Atmosphere Packaging - Adhikari, R.K.; Dhakal, D.D.; Gautam, D.M.; Thapa, R.B.; Tripathi, K.M.; Acedo, A.L.; Easdown, W.; Hughes, J.A.; Keatinge, J.D.H. (Nepalese Horticulture, 2018)
Abstract available with the full text.